(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the linguocultural features of phraseological units representing meteorological phenomena with a zoonymic component. On the material of the French language, phraseological units related to the phenomenon of meteorology with a zoonymic component were analyzed, and the cultural and historical foundations of the zoonyms included in them, their connection with meteorological phenomena, and the role of these units in the socio-cultural life of France were analyzed.